2016
DOI: 10.14260/jemds/2016/565
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in Outcomes of Excision Versus Invagination of Hernial Sac in Management of Indirect Inguinal Hernia

Abstract: BACKGROUNDThe newer belief is that ligature of richly innervated peritoneal sac is responsible for increased postoperative pain and other complications without any advantage in terms of recurrence rate. It is mainly due to the fact that ligation of richly innervated and well vascularised peritoneum produces a miniature peritonitis contributing to the post-operative discomfort and other complications. Aim of our study was to compare the difference in outcome of two different techniques of indirect inguinal hern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…2 Ranga HR et al, study mean post-operative pain score in group A was 2.8±0.764 while in group B was 2.68±0.69 with p value=0.568 , which was not statistically significant. 6 Delikoukos S et al, study mean post-operative pain score in group A was 2.8±1.4 and 2.3±1.2 in group B with p value <0.05. 5 In this study, mean post-operative pain score was 5.93±1.12 in group A and 4.39±1.03 in group B with P value 0.012, author observed that, lower pain score was reported among patients in group B…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…2 Ranga HR et al, study mean post-operative pain score in group A was 2.8±0.764 while in group B was 2.68±0.69 with p value=0.568 , which was not statistically significant. 6 Delikoukos S et al, study mean post-operative pain score in group A was 2.8±1.4 and 2.3±1.2 in group B with p value <0.05. 5 In this study, mean post-operative pain score was 5.93±1.12 in group A and 4.39±1.03 in group B with P value 0.012, author observed that, lower pain score was reported among patients in group B…”
Section: Discussionmentioning
confidence: 88%
“…4,5 An ideal hernia repair should be tension free, tissue based with no potential damage to vital structures, no long-term pain or complications and no recurrence. 6 Recurrences have frustrated surgeons of all ages, experience, skill and nationality. One of the cardinal causes for recurrence was thought to be failure to do high ligation of sac because of the emphasis on the sac, its ligation is done as a sacred ritual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation